Table of Content - - (Journal of Humanities & Social Sciences, 2023)
1. Natural disasters and their effects in Jerusalem in the Mamluk era (648 – 923 AH \ 1250 – 1516 AD)Mr. Hmydan Mahmoud Naji2. The aesthetic of Arabic calligraphy in Saudi plastic paintingCo-Prof. Maha Mohammed Alsudairy3. The impact of the COVID-19 pandemic on the females' Intention to buy clothes Online in Makkah regionMrs. Tahany Abdullah Abdul-Baqi Elias , Dr. Tagreed Saleh Ali Abalkhail4. The Reality of the Qatari Family and the Challenges Faced An Inter-generational Qualitative StudyMrs. Afrah Farhan Al-Otaibi , Mrs. Noura Hamad Al-Hajry , Mrs. Sarah Ali Al-Sallabi , Dr. Asmaa Malkawi5. Assessment of sustainable development in the urban poles status of the urban pole Retba (Municipality of Didouche Mourad-Constantine)Mrs. Haouari Souad6. The stance of Uday bin Hatim from the political developments in the Rashidi periodMr. Bader Haif bin Omerah7. The role of the medical social worker with patients with Complicated Grief disorderLecturer \ Norah Farhan Al-Anazi , Co-Prof. Husain Mohammed Al-Hakami
Keywords: Journal of Humanities & Social Sciences